Implementing Mobile Learning with Differentiated Instruction in Calculus: Student Learning Styles Analysis - Triana Harmini; Dihin Muriyatmoko; Siti Suprihatiningsih; Ebenezer Bonyah (Hipotenusa: Journal of Mathematical Society, 2025)
This study aims to examine: (1) differences in Calculus learning achievement between students using mobile learning with differentiated instruction (DI) and those using modules, (2) differences in achievement based on students' learning styles, and (3) the interaction between instructional methods and learning styles on learning outcomes. The participants were 112 Informatics Engineering students at Universitas Darussalam Gontor in the 2023/2024 academic year, divided into two groups: 59 students in the experimental group (using mobile learning) and 53 in the control group (using modules). The study was conducted over five sessions on the topic of Absolute Value Equations and Inequalities. A quasi-experimental method with a 2x3 factorial design was used. The research instruments included an achievement test and a learning style questionnaire. Data were analyzed using two-way ANOVA after confirming normality and homogeneity assumptions. The results showed that: (1) mobile learning with DI is more effective than modules, (2) learning styles significantly affect learning achievement, and (3) there is no interaction between instructional method and learning style. These findings suggest that mobile learning with DI can be effectively implemented regardless of students' learning styles and supports the development of inclusive digital learning environments in higher education.